Analysis of multidimensional poverty dynamics in Indonesia: The effect of demographic and institutional factors - Esha Najitama; Ghozali Maski; Asfi Manzilati (Journal of Innovation in Business and Economics, 2020)
Measuring poverty only from a monetary perspective is lacking. Given the variety of human needs, poverty needs to be measured multidimensionally. Hence, this study analyzes multidimensional poverty dynamics and identifies its determinants from the demographic and institutional factors. Using the Multidimensional Poverty Index (MPI) and data from the two survey periods of the Indonesia Family Life Survey (IFLS), it is known that multidimensional poverty tends to be transient rather than chronic. The highest education level of the head of the household, the level of dependency, the island of residence, the village political system, and the village government's corruption affect both chronic and transient poverty categories. The marital status of household heads, household size, and customary norms only affected the chronic poor category